Clinical and biological markers for predicting acute respiratory distress syndrome in sepsis patients: a systematic review and meta-analysis - Mardaningrat, Gede Ari Mahendra; Andrika, Putu; Putri, Isabella Soerjanto; Aryadi, I. Putu Hendri (International Journal of Research in Medical Sciences, 2024)
Sepsis is a serious condition that occurs when a person's immune system responds excessively to an infection, causing an inflammatory reaction that damages the body's organs. One of the complications that can occur in sepsis patients is acute respiratory distress syndrome (ARDS). Sepsis and ARDS are conditions with high mortality rates, so it is important to prevent them. This study aims to determine clinical and biological markers that can be used as a reference in predicting ARDS in sepsis patients, so that prevention efforts can be carried out quickly and precisely. We performed a search in two databases (PubMed and Cochrane) for articles published between January 1, 2013 and September 30, 2023 that reported markers or predictors of ARDS in sepsis patients. Eleven studies out of the 360 articles identified, met the inclusion criteria for this review. APACHE II score (MD 0.36; 95% CI=0.15-0.56), sequential organ failure assessment score (SOFA) score (Mean difference (MD)=0.50; 95% CI=0.04-0.97), CRP (MD=0.75; 95% CI=0.46-1.04), SP-D (MD=0.70; 95% CI=0.51-0.90), and serum receptor for advanced glycation end-products (sRAGE) (MD=0.72; 95% CI=0.59-0.84) have a significant influence on the incidence of ARDS in sepsis patients. Overall, the findings of a meta-analysis that included 11 studies involving 6,623 patients showed that the APACHE II score, SOFA score, CRP, SP-D, and sRAGE showed statistically significant values.